Shell-Isolated Nanoparticle-Enhanced Raman Spectroscopy - Krajczewski, Jan; Kudelski, Andrzej (Frontiers in Chemistry, 2019)
In 2010, Tian et al. reported the development of a new, relatively sensitive method of the chemical analysis of various surfaces, including buried interfaces (for example the surfaces of solid samples in a high-pressure gas or a liquid), which makes it possible to analyze various biological samples in situ. They called their method shell-isolated nanoparticle-enhanced Raman spectroscopy (SHINERS). SHINERS spectroscopy is a type of surface-enhanced Raman spectroscopy (SERS) in which an increase in the efficiency of the Raman scattering is induced by plasmonic nanoparticles acting as electromagnetic resonators that locally significantly enhance the electric field of the incident electromagnetic radiation. In the case of SHINERS measurements, the plasmonic nanoparticles are covered by a very thin transparent protective layer (formed, for example, from various oxides such as SiO2, MnO2, TiO2, or organic polymers) that does not significantly damp surface electromagnetic enhancement, but does separate the nanoparticles from direct contact with the probed material and keeps them from agglomerating. Preventing direct contact between the metal plasmonic structures and the analysed samples is especially important when biological samples are investigated, because direct interaction between the metal nanoparticles and various biological molecules (e.g. peptides) may lead to a change in the structure of those biomolecules. In this mini-review, the state of the art of SHINERS spectroscopy is briefly described.